2010
DOI: 10.1007/s10695-009-9313-y
|View full text |Cite
|
Sign up to set email alerts
|

Haematology and leucocyte enzyme cytochemistry of a threatened yellow catfish Horabagrus brachysoma (Gunther 1864)

Abstract: The haematology and leucocyte enzyme cytochemistry of Horabagrus brachysoma, a threatened freshwater catfish endemic to southern India, was studied using standard methods. Intra-specific variation was found for the haematological parameters, but this did not exceed the range of values observed in other catfishes. The relatively high haemoglobin (Hb) concentration may be indicative of an ability to breathe air and high activity. The erythrocytes are fully packed with Hb, revealing the bottom dwelling habit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 51 publications
5
24
1
Order By: Relevance
“…In the current study, no staining for alkaline phosphatase was obtained in any of the blood cells, as similarly reported in previous studies [9,26,34]. Also similar was the neutrophil intense staining for glycogen and Sudan black B, which is reported as findings in other fish species, such as Salminus maxillosus [29], Ictalurus punctatus [40], Thunnus maccoyii [41].…”
Section: Cytochemistrysupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, no staining for alkaline phosphatase was obtained in any of the blood cells, as similarly reported in previous studies [9,26,34]. Also similar was the neutrophil intense staining for glycogen and Sudan black B, which is reported as findings in other fish species, such as Salminus maxillosus [29], Ictalurus punctatus [40], Thunnus maccoyii [41].…”
Section: Cytochemistrysupporting
confidence: 91%
“…The presence of esterase in fat snook thrombocytes is certainly another evidence of the participation of this cell in the innate immune response as suggested by other authors [9,32,34,38]. Furthermore, the presence of glycogen in thrombocytes fits the assumption of the potential phagocytic role of this cell as the source of energy needed to the process of digestion and elimination of foreign substances [5,12,39].…”
Section: Cytochemistrysupporting
confidence: 57%
“…Previous studies, on the other hand, reported increased total protein concentrations in the blood plasma of Tinca tinca broodstock before reproduction time (25,26). Blood glucose is a highly variable parameter that is strongly influenced by handling and environmental stresses as well as seasonal variations, nutritional status, and sexual maturity, among other stressors (27). Glucose levels in the female broodstock were significantly lower than levels in the male broodstock determined by this study.…”
Section: Rivercontrasting
confidence: 61%
“…Fish thrombocytes represent a link between innate and adaptive immunity (Passantino et al 2005) and express surface and intracellular molecules that are involved in immune function (Kollner 2004). It is already recognised that fish thrombocytes are blood phagocytes that form one a protective barrier (Tavares-Dias and Moraes, 2004;Prasad and Charles 2010;Prasad and Priyanka 2011). Haematological studies contribute to an understanding of the relationship between blood characteristics and the habitat and the adaptability of the species to the environment, so there is a need for establishing normal haematological values in different species of fish.…”
Section: Discussionmentioning
confidence: 99%